European natural gas supply secure despite political crises - Hella Engerer; Franziska Holz; Philipp M. Richter; Christian von Hirschhausen; Claudia Kemfert (DIW Economic Bulletin, 2014)
Natural gas is a significant contributor to European energy supply. Hence, the political crisis between Russia and Ukraine increases fears of the consequences of Russia suspending natural gas supplies to Ukraine and the European Union. The last time this had occurred was in the winter of 2009 when Russia and Ukraine disputed about the price of natural gas and transit costs. However, the European Union has subsequently increased the security of its gas supply. Progress has been made in implementing the measures proposed by the European Commission, particularly the diversification of supply sources and the expansion of natural gas infrastructure to secure supply from various countries. The opportunities to ease temporary supply bottlenecks have improved significantly within the Union in recent years. Nevertheless, Russia remains a major supplier of natural gas to the EU. The Russian gas company Gazprom plays a key role in Eastern Europe and is also gaining importance in Germany. However, this dependency is not a one-way street: Russia generates high export revenues from its natural gas trade and currently has few alternatives to exporting to the EU. Model calculations by DIW Berlin show that Europe can largely cope with a supply disruption by Russia via Ukraine. Some Eastern European countries, however, would struggle to fully offset a complete suspension of Russian supply. To further increase supply security in Europe in the medium term, it will be necessary to continue diversifying gas supplies, particularly by making more efficient use of existing infrastructure, and expanding pipelines and capacity to import liquefied natural gas. Additionally, Europe should consider setting up strategic gas reserves. Another important step would be to continue to improve energy efficiency in all sectors and consistently expand renewable energy sources as part of the European energy and climate strategy.
Keywords: Q34; L95; C6; 330; natural gas; supply security; Europe; modeling